Planning distribution network using the multi-agent game and distribution system operators - Li, Jiangnan; Wang, Tao; Tang, Shouquan; Jiang, Jiru; Chen, Shuyao (Frontiers in Energy Research, 2023)
When planning the distribution network, the income of each market entity is calculated by fixed price. How to take the price of power into account while developing the planning strategy for each organization in the actual power market is an urgent issue that needs to be addressed imminently. To address this problem, considering the continuous change of the market price due to the change of supply-demand relationship in the actual power market, this article proposes a distribution network planning method which considers the distribution system operator (DSO) and multi-agent game. Firstly, the planning decision model of distribution network companies and power users with different interest subjects is constructed with grid planning and DG operation as decision variables. Secondly, DSO is introduced to the game framework. Based on distribution locational marginal price (DLMP), a price accounting model is being developed. Then, the transfer relationships and game behavior among distribution company, power users and DSO are analyzed. Finally, an iterative search algorithm is used to solve a multi-agent game planning model of a distribution network that takes into account price signals in the power market. Examples based on IEEE33-bus systems validate the suggested method's validity and efficacy.